CONTEMPORARY DAWAH STRATEGIES IN DEVELOPING THE RELIGIOUS LIFE OF THE COMMUNITY OF LAU GUMBA VILLAGE BERASTAGI DISTRICT KARO REGENCY - Nazrial Amin; Muhammad Yunan Harahap (Proceeding International Seminar of Islamic Studies, 2022)
Contemporary da'wah strategy is not easy to do by preachers, especially in the midle of minority communities and religious understanding is still very low. The da'i need intelligence so that there is no horizontal conflict. This study aimed to find out how contemporary da'wah strategies were in fostering religious life and the supporting factors and difficulties of contemporary da'wah strategies in fostering community life in Lau Gumba Village, Berastagi District, Karo Regency. This research method were Field Research (field study) and Library Research (library study). The field method was done by interview technique while the library method was based on primary data. The results of the research showed that the strategies used were: 1. Preaching through media and tools, such as used inFocus and PowerPoint slides to make it easier for people to understand the material. 2. Approached to religious leaders, village heads and customs with the understanding of religious moderation that upholded the values of religious tolerance. The difficulty in this strategy was : the understanding of religion was still low, while the supporting factor was the high motivation of the community to maintain religious harmony through a good understanding of religion.Keywords: Strategy, Da'wah, Contemporary